2020
DOI: 10.1029/2020gl087268
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric Multiscale Observation of an Electron Diffusion Region at High Latitudes

Abstract: On 17 October 2016, Magnetospheric Multiscale (MMS) sampled an electron diffusion region (EDR) embedded in an electron‐scale current sheet within a mixed portion of the high‐latitude magnetosheath adjacent to the magnetopause. We analyze the generalized Ohm's law, dissipation, and electron velocity distributions inside the EDR. The velocities, magnetic fields, and densities observed in the magnetosheath and magnetosphere indicate the magnetopause was unstable to the Kelvin‐Helmholtz instability, which can form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…This study shows that KHI occurs relatively often at Jupiter's dawn magnetopause when compared to Earth (∼19% of the time) and Saturn (∼14% of the time) (Burkholder et al, 2020;Kavosi & Raeder, 2015). These results agree with models and simulations regarding the viscous interactions that take place along the dawn flank of the magnetopause, a region in which KH waves grow and develop from the subsolar region and advect tailward as the solar wind is draped over the highly variable magnetopause (Delamere & Bagenal, 2010;Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study shows that KHI occurs relatively often at Jupiter's dawn magnetopause when compared to Earth (∼19% of the time) and Saturn (∼14% of the time) (Burkholder et al, 2020;Kavosi & Raeder, 2015). These results agree with models and simulations regarding the viscous interactions that take place along the dawn flank of the magnetopause, a region in which KH waves grow and develop from the subsolar region and advect tailward as the solar wind is draped over the highly variable magnetopause (Delamere & Bagenal, 2010;Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…The spacecraft moves in and out of magnetosheath and magnetosphere plasma, crossing the boundary several times. At Saturn's dawn magnetopause, KH vortices were observed at a 14% occurrence rate and an 18% occurrence rate from 10 to 12 local time, where there may be a stationary KH vortex (Burkholder et al, 2020). Using a boundary normal analysis approach, Masters et al (2009) identified regular surface waves present at magnetopause crossings that were characteristic of KH waves via Cassini observations.…”
Section: Investigating the Occurrence Of Kelvin-helmholtz Instabiliti...mentioning
confidence: 99%
“…If we express truek^ $\hat{\mathbf{k}}$ in terms of the spherical angles ϕ and θ , the percent of the 4 π solid angle that satisfies the KHI instability criteria at a given location may be calculated. We term this percentage the “unstable solid angle” (Burkholder et al., 2020; Nykyri et al., 2021). Events with larger unstable solid angles are likely to be KHI.…”
Section: Methodsmentioning
confidence: 99%
“…A snapshot of any given field line would likely reveal bidirectional electron beams. Such beams are commonly observed in KH active regions of the terrestrial magnetopause boundary (Burkholder et al, 2020b). Nykyri et al (2021) suggested that, among other mechanisms, magnetic reconnection could be a candidate for explaining the > 100 eV counter-streaming electrons observed by the Magnetosphere Multiscale mission.…”
Section: Heavy Ion Effectsmentioning
confidence: 97%